Wavelength Tuning of Multimode Interference Fiber Lasers: A Review. Issue 8 (28th May 2021) - Guzman-Sepulveda, Jose Rafael; Castillo-Guzman, Arturo Alberto
Abstract : Herein, the main aspects of fiber lasers are summarized where multimode interference (MMI) is the underlying phenomenon for the wavelength tuning mechanism. Also, 15 years of work in the field are covered, from its first report, in 2005, to the most recent publications, in 2020. In addition to the historical perspective, insights into the different mechanisms are also provided that are exploited to tune the spectral response of the MMI filters used in fiber lasers, among which are free space, optofluidic, stress optic, thermo optic, and nonlinear mechanisms. Abstract : Herein, the main aspects of fiber lasers which are wavelength‐tuned based on multimode interference phenomena are summarized. Also, 15 years of work in the field are covered. In addition to a historical perspective, insights into the different mechanisms are provided that are exploited among which are free space, optofluidic, stress optic, thermo optic, and nonlinear mechanisms.